Penguatan Peran Komunikasi Kader Dalam Pembangunan Kampung KB Di Kelurahan Sungai Jingah Kota Banjarmasin - Dewi Merdayanty; Didi Susanto; Junaidi Junaidi (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The aim of implementing community service is to strengthen the role of cadre communication in supporting the success of the development of the Family Planning Village program in Sungai Jingah Village, Banjarmasin City and teaching recommended by Islam regarding ways of communicating. The method used is through lectures and questions and answers. The implementation of the KB Village program activities in the Sungai Jingah Village, Banjarmasin City, at the workshop stage, provided the concept of understanding the concepts and indicators of success of the KB Village as well as assigning KB Village cadres to be given training so that each cadre can convey information and educational communications to community members. The role of communication as a factor that can support the success of developing the Family Planning Village program for the community in Sungai Jingah Village, Banjarmasin City through (1) Communication, information and individual education or home visits to target homes ; (2) Communication, information and group education by utilizing social forums ; (3) Mass communication, information and education by utilizing traditional media or people's entertainment programs; (4) Communication, information and counseling education by utilizing community consultation organization platforms to be more targeted. Islam teaches about ways of communicating, which consist of several forms, namely (1) qaulan Ma'ruf, (2) Qaulan Baliighaa , (3) qaulan Sadida , (4) Qaulan Karima , (5) Qaulan Maisuura , (6) Qaulan Layyinan , (7) Qaulan Tsaqiila .